Behavioral Models of Tinnitus and Hyperacusis in Animals - Hayes, Sarah H.; Radziwon, Kelly E.; Stolzberg, Daniel J.; Salvi, Richard J. (Frontiers in Neurology, 2014)
The phantom perception of tinnitus and reduced sound level tolerance associated with hyperacusis, have a high comorbidity and can be debilitating conditions for which there are no widely accepted treatments. One factor limiting the development of treatments for tinnitus and hyperacusis is the lack of reliable animal behavioral models of these disorders. Therefore, the purpose of this review is to highlight the current animal models of tinnitus and hyperacusis, and to detail the advantages and disadvantages of each paradigm. To date, this is the first review to include models of both tinnitus and hyperacusis.